Plasmon-enhanced multi-photon excited photoluminescence of Au, Ag, and Pt nanoclusters - Bornacelli, J; Torres-Torres, C; Crespo-Sosa, A; Reyes-Esqueda, J A; Oliver, A (Nanotechnology, 2024)
In this work, we have studied the multi-photon excited photoluminescence from metal nanoclusters (NCs) of Au, Ag and Pt embedded in Al O matrix by ion implantation. The thermal annealing process allows to obtain a system composed of larger plasmonic metal nanoparticles (NPs) surrounded by photoluminescent ultra-small metal NCs. By exciting at 1064 nm, visible emission, ranging from 450 to 800 nm, was detected. The second and fourth-order nature of the multiphoton process was verified in a power-dependent study measured for each sample below the damage threshold. Experiments show that Au and Ag NCs exhibit a four-fold enhanced multiphoton excited photoluminescence with respect to that observed for Pt NCs, which can be explained as a result of a plasmon-mediated near-field process that is of less intensity for Pt NPs. These findings provide new opportunities to combine plasmonic nanoparticles and photoluminescent nanoclusters inside a robust inorganic matrix to improve their optical properties. Plasmon-enhanced multiphoton excited photoluminescence from metal nanoclusters may find potential application as ultrasmall fluorophores in multiphoton sensing, and in the development of solar cells with highly efficient energy conversion modules.